THE ABILITY OF THE FIELD EXTENSION OFFICERS TO IMPLEMENT COMMUNICATIVE EXTENSION TEACHING TECHNIQUE IN JAMBI CITY - Denny Denmar; Ferdiaz Saudagar (Dinasti International Journal of Education Management And Social Science, 2020)
The objective of the study is to find out the ability of the field extension officers to implement communicative extension teaching technique, knowledge of extension, extension score, and creative attitude. The study was conducted in Jambi Extension Center (2019) with 90 respondents randomly selected. The study shows that there are positive correlations between: 1) knowledge of extension and the ability of the field extension officers to implement communicative extension teaching technique; 2) extension score and the ability of the field extension officers to implement communicative extension teaching technique; 3) creative attitude and the ability of the field extension officers to implement communicative extension teaching technique. In addition, there is a positive correlation between knowledge of extension, extension score and creative attitude & the ability of the field extension officers to implement communicative extension teaching technique Thus, the ability of the field extension officers to implement communicative extension teaching technique can be enhanced by increasing knowledge of extension, extension score, and creative attitude.